Manipulating the Composition and Structure of Solid Electrolyte Interphase at Graphite Anode by Adjusting the Formation Condition. Issue 9 (5th June 2019) - Zhu, Taohe; Hu, Qiyang; Yan, Guochun; Wang, Jiexi; Wang, Zhixing; Guo, Huajun; Li, Xinhai; Peng, Wenjie
Abstract : The solid electrolyte interphase (SEI) plays an important role in the comprehensive electrochemical performance of lithium‐ion batteries. However, graphite generates a 10% volume expansion during cycles, resulting in structural cracking of the SEI and further electrolyte decomposition. Herein, by adjusting the formation current density, the composition and structure of the SEI are regulated to optimize the electrochemical performance of graphite electrodes. The results manifest that the SEI is mainly formed between 1.1 and 1.4 V, and a lower formation current density is favorable for forming an excellent SEI at the graphite electrode surface. The SEI formed under such condition possesses more organic lithium salts and less inorganic lithium salts, and it is enwrapped onto the surface of the graphite anode more uniformly as compared with higher formation current density. Meanwhile, the derived SEI is more stable and thicker, which can effectively stabilize the interface of the electrode/electrolyte to enhance the cyclic stability of graphite anode materials after the formation step, so as to buffer its volume change during the cycles. Abstract : The effect of formation current density on the chemical properties of the solid electrolyte interphase (SEI) is revealed. The results manifest that a lower formation current density is favorable for forming more stable and thicker SEI at the graphite anode, which can effectively stabilize the interface of the electrode/electrolyte to enhance the cyclic stability of graphite after the formation step.